1999
DOI: 10.1523/jneurosci.19-10-03801.1999
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Amphetamine- and K+-Mediated Dopamine Release in Rat Striatum after Repeated Amphetamine: Differential Requirements for Ca2+- and Calmodulin-Dependent Phosphorylation and Synaptic Vesicles

Abstract: After cessation of repeated, intermittent amphetamine, we detected an emergent Ca 2ϩ -dependent component of amphetamine-induced dopamine release and an increase in calmodulin and Ca 2ϩ -and calmodulin-dependent protein kinase activity in rat striatum. This study examined the involvement of calmodulin-dependent protein kinase II (CaM kinase II) and synaptic vesicles in the enhanced Ca 2ϩ -dependent dopamine release in response to amphetamine or K ϩ in rat striatum. Rats were pretreated for 5 d with 2.5 mg/kg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 24 publications
5
60
1
Order By: Relevance
“…Hence, we obtained evidence for a model in which CaMKII␣ binding to a domain corresponding to the last 24 C-terminal residues facilitates N-terminal phosphorylation and thereby AMPH-induced DA efflux (17). The model concurs with data suggesting that CaMKII␣ is activated upon AMPH administration (23,24) possibly as a consequence of elevated intracellular calcium levels through still poorly understood mechanisms (25). Impaired AMPH-induced efflux in synaptosomes from mice with ablated CaMKII␣ activity has provided further indirect support for the model (26).…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Hence, we obtained evidence for a model in which CaMKII␣ binding to a domain corresponding to the last 24 C-terminal residues facilitates N-terminal phosphorylation and thereby AMPH-induced DA efflux (17). The model concurs with data suggesting that CaMKII␣ is activated upon AMPH administration (23,24) possibly as a consequence of elevated intracellular calcium levels through still poorly understood mechanisms (25). Impaired AMPH-induced efflux in synaptosomes from mice with ablated CaMKII␣ activity has provided further indirect support for the model (26).…”
supporting
confidence: 86%
“…Notably, such a function of PICK1 has been proposed in relation to its binding to ASIC1/2 (acid-sensing ion channels 1/2) and the GluR2 subunit of the AMPA receptor (40,41). It has also previously been suggested that PKC isoforms, including PKC␣ and PKC␤, might play a role in AMPH-mediated DA efflux (17,23,(42)(43)(44). Furthermore, the dominant-negative TAT-C24WT peptide would be predicted to abolish not only the association of CaMKII␣ to endogenous DAT but also the association of the PDZ domain protein PICK1 (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microinjection of calcium channel antagonists into the NAC dose-dependently impaired behavioral sensitization to cocaine without altering the acute locomotor response to this psychostimulant (Pierce et al 1998). Similarly, other experiments revealed that the sensitized DA release in the NAC induced by amphetamine is calcium-dependent and can be attenuated by a selective calmodulin-dependent protein kinase II inhibitor, whereas DA release induced by a single dose of amphetamine is calcium-independent (Carboni et al 1989;Warburton et al 1996;Pierce and Kalivas 1997b;Kantor et al 1999). Thus, one may hypothesize that blockade of NT receptors alters the behavioral sensitized response to amphetamine by acting on the calcium-dependent portion of the DA response to amphetamine.…”
Section: Discussionmentioning
confidence: 90%
“…In vitro, these antibodies can induce increases in the activity of calcium/calmodulin-dependent protein kinase II (CaM kinase II), which in turn can lead to increases in dopamine production and release. CaM kinase II activation is a potential mechanism by which clinical symptoms ensue (Roberts-Lewis et al 1986;Kantor et al 1999). The anti-carbohydrate A antibody measures the immune response to N-acetyl-beta-dglucosamine (Bloem et al 1988).…”
Section: Serologic and Prospective Studiesmentioning
confidence: 99%